The spread of Mandarin in Malaysia: Evidence in language choices in public settings - Wang, Xiaomei (Journal of Modern Languages, 2017)
Adopting Cooper’s (1982) framework of language spread, this paper focuses on the spread of Mandarin in the Chinese community in the state of Johore, Malaysia. Survey results published by the present author already show some evidence of the spread of Mandarin among Chinese Malaysians. Specifically, those previous studies have focused on language choices in the family domain (Wang, 2007) and the role of mass media played in the process of Mandarin spread (Wang, 2005, 2006a). The present study complements the previous ones by focusing on the language choice behaviors in public sellings. Observations on language use were made in public places such as shopping centers, night markets, food stalls, and coffee shops. Unintrusive observation techniques complement the instrument of questionnaire used in previous surveys. 201 interactions between 102 sales persons and customers were recorded in the observation form by the researcher. Four towns in the state were chosen for the study, namely Johor Baru, Kluang, Batu Pahat and Muar. The results show the spread of Mandarin among the Chinese Malaysians in the towns studied. Age and gender are proven to be two significant factors influencing the language choice of the sales persons and the customers. The younger the speakers are, the more Mandarin is used during the interactions. Meanwhile, the female speakers tend to use more Mandarin than the male speakers. Slightly significant difference is found across 6 public settings in terms of language choice. However, who speaks first is not a significant factor influencing the language choice in the interaction. Present findings complement previous ones: Mandarin is gaining ground not only in private settings, but also in public settings, where Chinese dialects used to dominate.